PENGARUH KOMUNIKASI VERTICAL DAN KOMUNIKASI HORIZONTAL TERHADAP KINERJA KARYAWAN PADA PT.KALTIM DIAMOND COAL SITE LOA GAGAK KUTAI KARTANEGARA - Silpiter Sului (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
This research aim to to test vertical communications and communications of horizontal by simultan have an effect on signifikan to employees performance, to test vertical communications and communications of horizontal by parsial have an effect on signifikan to employees performance and to test among vertical communications and communications of horizontal most having an effect on [of] signifikan to employees performance at PT. Kaltim Diamond Coal Site Loa Crow of Kutai Kartanegara.This Type Research of researcher use quantitative research, with amount of sampel rounded up to become 86 research sampling employees the used propabilitas sampel. used Data analysis in the form of used doubled linear regresi to know influence of independent variable (X) which consist of vertical communications (X1) and communications of horizontal (X2) to variable of dependen that is Performance Employees ( Y).Result of research of showed that doubled linear regression test by simultan found that entire/all independent variable that is Vertical Communications and Communications of Horizontal have an effect on signifikan to variable of dependen Performance Employees at PT. Kaltim Diamond Coal Site Loa Crow of Kutai Kartanegara, by parsial found that independent variable that is Vertical Communications not have an effect on signifikan to variable of dependen Performance Employees and Communications of Horizontal have an effect on signifikan to variable of dependen Performance and variable test most having an effect on to be known that Communications variable of Horizontal represent most having an effect on variable to Performance Employees at PT. Kaltim Diamond Coal Site Loa Crow of Kutai Kartanegara.